Interprofessional Healthcare Students' Attitudes, Skills, and Knowledge After Comprehensive Pain Assessment Training in Verbal and Nonverbal Patients. Issue 4 (13th August 2021) - Cook, Heather; Kaiser, Karen Snow; Walker, Kathryn A.; McPherson, Mary Lynn
Abstract : A comprehensive pain assessment is the first step in safe, effective pain management. Few studies have explored variations of strategies and measures for multidimensional pain assessment education in both verbal and nonverbal patients. In this retrospective cohort study, interprofessional health care students enrolled in a palliative care curriculum completed a pain assessment training, which taught the PQRSTA ("palliating factors, precipitating factors, previous treatments, quality, region, radiation, severity, temporal factors and associated symptoms") mnemonic as a strategy for assessing pain in verbal patients and the Pain Assessment in Advance Dementia and Checklist of Nonverbal Pain Indicators measures for nonverbal patients. The purpose of this study was to compare the change in attitudes, self-perceived skills, and knowledge regarding pain assessment before and after the training. Attitudes and self-perceived skills were assessed in the pretraining and posttraining survey, which was analyzed using χ 2 test or Fisher exact test. Students' knowledge responses were analyzed using Wilcoxon signed rank test to assess accuracy of responses compared with the expert defined score. One hundred eighty-two students were included. Results showed a statistically significant improvement in attitudes related to applicability of pain measures and self-perceived skills. Overall, data did not support an increase in knowledge using the PQRSTA mnemonic, or Pain Assessment in Advance Dementia and Checklist of Nonverbal Pain Indicators measures. Future pain trainings should consider training on only 1 nonverbal pain measure, incorporating bedside assessments, and integrating real-time feedback.